Development of Chemistry Edutainment Learning Media to Enhance Students Retention - Nisa, Chairun; Kurniasih, Dedeh; Hadiarti, Dini; Kurniati, Tuti (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The teaching media that a teacher uses can have an impact on the comprehension and memory of the students. Chemical bonding material is one of the learning resources that educators are encouraged to employ to assist and promote more creative, engaging, and enjoyable learning experiences. Chemistry Edutainment media is one type of educational resource that can be employed. This study attempts to characterize student learning retention following chemistry lessons using chemistry edutainment on chemical bond material for class X MAN 3 Pontianak, as well as to ascertain the validity, practicality, and efficacy of chemistry edutainment media. The methods of measurement, observation, and interviewing are employed in the data collection process. Student learning outcomes assessments, observation sheets, and interview sheets were the instruments utilized to collect the data. The study employs the ADDIE method, yielding validation rates of 93.3% for the material aspect and 90.6% for the media aspect. These percentages denote a high level of validity. The practicality percentages, derived from the initial and main field trial questionnaire responses, are 87.17% and 94.03%, respectively, indicating a high degree of practicality. Moreover, the effectiveness analysis, based on the learning outcomes following the use of Chemistry Edutainment media, resulted in N-Gain scores of 0.92 and 0.71 for the initial and main field trials, respectively, meeting the high effectiveness criteria. The retention percentages obtained in the initial and main field trials are 75% and 89.97%, respectively, which meet the high retention criteria.